Thermally conductive sheet
By introducing crosslinking resin and directionally arranged boron nitride into the thermally conductive sheet, the durability problem of the thermally conductive sheet under high temperature and pressure changes is solved, and a thermally conductive sheet with high durability and good thermal conductivity is achieved.
Patent Information
- Application Number
- JP2023123744
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing thermal conductivity sheets are insufficient in durability under high temperature and pressure changing conditions, and cannot effectively maintain good thermal conductivity.
Using a thermally conductive sheet containing a crosslinking resin and a boron nitride, the boron nitride is arranged at an orientation angle of 60° to 90°, and the boron nitride accounts for more than 50% of the total volume of the sheet. Combining the crosslinking resin and other components, a crosslinking structure is formed by processing at a specific pressure and temperature to improve durability.
The high durability and good thermal conductivity of the thermally conductive sheet under high temperature and pressure changes are achieved, ensuring effective heat dissipation and stability of use of electronic components.
Smart Images

Figure 2025019870000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet. [Background technology]
[0002] In recent years, the amount of heat generated by electronic components such as power semiconductors (e.g., IGBT modules) and integrated circuit (IC) chips has increased as their performance has improved. As a result, it has become necessary to take measures to prevent functional failures caused by temperature increases in electronic devices that use these components.
[0003] As a countermeasure against functional failures caused by temperature rises in electronic components, a method is generally adopted in which a heat sink, heat sink plate, heat sink fin, or other heat sink made of metal is attached to the heat generating body of the electronic component to promote heat dissipation. When using a heat sink, in order to efficiently transfer heat from the heat generating body to the heat sink, a sheet-like member with high thermal conductivity (thermal conductive sheet) is placed between the heat generating body and the heat sink, and a certain pressure is applied to the thermal conductive sheet to bring the heat generating body and the heat sink into close contact with each other.
[0004] Thermally conductive sheets are required to have high insulating properties. For example, Patent Document 1 describes that in a thermally conductive sheet containing a fluororesin and a thermally conductive filler containing boron nitride particles, the content of the thermally conductive filler in the sheet is 30 volume % or more and 75 volume % or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-203857 A Summary of the Invention [Problem to be solved by the invention]
[0006] Here, when the thermally conductive sheet is used, it is exposed to high temperatures due to heat generated by the heating element when the electronic device is in operation. Furthermore, pressure may be applied to the thermally conductive sheet due to the expansion of members such as the heating element and the heat sink at high temperatures. Such pressure may be relieved by the members decreasing in temperature and shrinking due to the stopping of operation of the heating element, i.e., electronic components, etc. Thermally conductive sheets used under such conditions are required to maintain good thermal conductivity, in other words, to have excellent durability of thermal conductivity, even when exposed to changes in pressure conditions caused by the expansion and contraction of members.
[0007] However, the above-mentioned conventional heat conductive sheets have room for improvement in terms of durability of heat conductivity.
[0008] Therefore, an object of the present invention is to provide a thermally conductive sheet having excellent durability of thermal conductivity. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to achieve the above object, and have newly discovered that a thermally conductive sheet containing a resin including a crosslinked resin and boron nitride in a predetermined volume ratio, in which the boron nitride is oriented at a predetermined orientation angle within the sheet, has excellent durability of thermal conductivity when the value of the recovery rate calculated according to a predetermined formula is 60% or more, and have completed the present invention.
[0010] That is, the present invention aims to advantageously solve the above-mentioned problems, and is characterized in that [1] the thermal conductive sheet of the present invention is a thermal conductive sheet containing a resin and boron nitride particles, wherein the resin contains a crosslinked resin, the boron nitride particles are oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the thermal conductive sheet, the volume fraction of the boron nitride particles in the total volume of the resin and the boron nitride particles is 50 volume% or more, and the value of the recovery rate calculated according to the following formula (1) is 60% or more, where T1 (mm) is the initial thickness of the thermal conductive sheet, T2 (mm) is the thickness during pressure which is the thickness when the thermal conductive sheet is pressurized for 10 seconds under conditions of a temperature of 100°C and 1 MPa, and T3 (mm) is the post-pressure thickness which is the thickness 1 minute after the pressurized thermal conductive sheet is unloaded. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1) The thermally conductive sheet of the present invention has excellent durability of thermal conductivity. In this specification, the orientation angle of boron nitride particles can be measured by the method described in the examples of this specification.
[0011] [2] Here, in the thermally conductive sheet of [1] above, the cross-linked resin preferably contains at least one cross-linked product of an acrylic polymer, an acrylonitrile-butadiene copolymer, and a styrene-butadiene copolymer. If the thermally conductive sheet contains a cross-linked product of any of the above polymers, the thermal conductivity durability is further improved.
[0012] [3] In the thermal conductive sheet of [1] or [2], the volume fraction of the crosslinked resin in the total volume of the resin and the boron nitride particles is preferably 10% by volume or more. If the volume fraction of the crosslinked resin in the thermal conductive sheet is 10% by volume or more, the durability of thermal conductivity is further improved.
[0013] [4] In addition, in any one of the thermally conductive sheets [1] to [3] above, the compressibility calculated according to the following formula (2) is preferably 12% or more and 42% or less. Compression rate (%) = (1 - (T2 ÷ T1)) × 100 (%) (2) A thermally conductive sheet that satisfies these attributes has even greater durability in thermal conductivity.
[0014] [5] Furthermore, in any of the thermal conductive sheets [1] to [4] above, a voltage is applied to the thermal conductive sheet at a voltage increase rate of 0.6 kV / sec to obtain a voltage V1 (kV) when the current flowing through the thermal conductive sheet becomes 10 mA, and the obtained voltage V1 (kV) is divided by the initial thickness T1 (mm) of the thermal conductive sheet, so that the value of the withstand voltage test (kV / mm) is preferably 8 (kV / mm) or more. A thermally conductive sheet that satisfies these attributes has excellent insulating performance. Effect of the Invention
[0015] According to the present invention, it is possible to provide a thermally conductive sheet having excellent durability in thermal conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described in detail. Since the thermally conductive sheet of the present invention has thermal conductivity, it can be used by being sandwiched between a heat generating body and a heat dissipating body. For example, the thermally conductive sheet of the present invention can be used to form an electronic device by being interposed between a heat generating body such as a semiconductor, an electronic display, or a general electronic component and a heat dissipating body such as a heat sink, a heat dissipating plate, or a heat dissipating fin to bond them together.
[0017] (Thermal Conduction Sheet) The thermal conductive sheet of the present invention includes a resin and boron nitride particles. The thermal conductive sheet of the present invention may further include a component (other component) other than the resin and the boron nitride particles. The thermal conductive sheet of the present invention includes a crosslinked resin. The boron nitride particles contained in the thermal conductive sheet are oriented at an orientation angle of 60° to 90° with respect to the main surface of the thermal conductive sheet. Furthermore, in the thermal conductive sheet, the volume fraction of the boron nitride particles in the total volume of the resin and the boron nitride particles is 50% by volume or more. The thermal conductive sheet of the present invention is characterized in that the value of the recovery rate calculated according to the following formula (1) is 60% or more, where T1 (mm) is the initial thickness of the thermal conductive sheet, T2 (mm) is the thickness during pressure when the thermal conductive sheet is pressed for 10 seconds under conditions of a temperature of 100°C and 1 MPa, and T3 (mm) is the thickness after pressure is applied 1 minute after the pressed thermal conductive sheet is unloaded. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1)
[0018] The thermally conductive sheet of the present invention contains a resin containing a crosslinked resin at a predetermined volume fraction, contains boron nitride particles oriented in a predetermined direction, and has a restoration rate calculated according to the above formula (1) of 60% or more, and therefore has excellent durability of thermal conductivity. This is presumably because a thermally conductive sheet containing a crosslinked resin and oriented boron nitride particles and satisfying the above attributes regarding the restoration rate has an appropriate strength and elasticity of the crosslinked resin, which satisfies the above attributes regarding the restoration rate, thereby favorably maintaining the oriented structure of the boron nitride particles inside the thermally conductive sheet and allowing the thermally conductive sheet to favorably follow the expansion and contraction of the member to which it is applied.
[0019] <Resin> The heat conductive sheet of the present invention contains a resin, so that the heat generating body and the heat dissipating body can be well adhered to each other via the heat conductive sheet. In this specification, rubber and elastomer are included in the "resin". The resin that may be contained in the thermally conductive sheet of the present invention constitutes a matrix resin, and also functions as a binder that binds the boron nitride particles together. The resin contained in the thermal conductive sheet of the present invention contains a crosslinked resin, and optionally contains a resin other than the crosslinked resin (other resin).
[0020] <<Crosslinked resin>> The resin contained in the thermal conductive sheet of the present invention contains a crosslinked resin. The crosslinked resin is a resin crosslinked by a crosslinking agent. The thermal conductive sheet of the present invention contains a crosslinked resin as a resin, and thus has appropriate strength and elasticity, and is therefore excellent in durability of thermal conductivity.
[0021] Here, the crosslinked resin is preferably a resin that is solid at room temperature and normal pressure. In this specification, "room temperature" refers to 23° C., and "normal pressure" refers to 1 atm (absolute pressure).
[0022] The crosslinked resin is formed by crosslinking the crosslinkable resin with the crosslinking agent. In the crosslinking reaction, a crosslinking accelerator can be used. The crosslinking agent is not particularly limited, but for example, hexamethylenediamine carbamate as an amine-based crosslinking agent or sulfur can be used.
[0023] [Crosslinkable resin] The crosslinkable resin is not particularly limited, and although it depends on the types of the crosslinking agent and the crosslinking accelerator, for example, a resin that is solid at room temperature and normal pressure can be used. Note that, in order to prevent the crosslinkable resin from becoming excessively hard and losing elasticity, it is preferable that the crosslinkable resin does not contain an epoxy group, in other words, is a resin other than an epoxy resin.
[0024] - A resin that is solid at room temperature and pressure - Examples of resins that are solid under normal temperature and pressure include acrylic polymers such as poly(2-ethylhexyl acrylate), copolymers of acrylic acid and 2-ethylhexyl acrylate, polymethacrylic acid or its ester, and polyacrylic acid or its ester; styrene-acrylonitrile copolymers; acrylonitrile-butadiene-styrene copolymers (ABS resins); styrene-butadiene copolymers or their hydrogenated products; acrylonitrile-butadiene copolymers (nitrile rubber); styrene-butadiene block copolymers or their hydrogenated products; styrene-isoprene block copolymers or their hydrogenated products; silicone resins such as polyimide silicone resins; fluororesins such as vinylidene fluoride-based fluororesins, tetrafluoroethylene-propylene-based fluororesins, and tetrafluoroethylene-purofluorovinyl ether-based fluororesins. These may be used alone or in combination of two or more. Among these, it is preferable that the thermally conductive sheet of the present invention contains a crosslinked resin that is a crosslinked product formed using at least one of an acrylic polymer, an acrylonitrile-butadiene copolymer, and a styrene-butadiene copolymer.
[0025] The crosslinkable resin preferably has a glass transition temperature of -50.0°C or higher, more preferably -35.0°C or higher, even more preferably -30.0°C or higher, and preferably -8.0°C or lower, more preferably -15.0°C or lower, and even more preferably -20.0°C or lower. If the glass transition temperature of the resin used as the crosslinkable resin is equal to or higher than the lower limit, the restorability of the obtained heat conductive sheet can be further improved, and as a result, the durability of the heat conductivity can be further improved. If the glass transition temperature of the resin used as the crosslinkable resin is equal to or lower than the upper limit, the obtained heat conductive sheet can be given appropriate flexibility, and as a result, the durability of the heat conductivity can be further improved.
[0026] <<Other resins>> The resin other than the crosslinkable resin is not particularly limited, but includes a resin that does not undergo a crosslinking reaction with the crosslinking agent and crosslinking accelerator that contribute to the crosslinking of the crosslinkable resin. For example, a liquid resin that is liquid at room temperature and normal pressure can be used as such a resin. For example, a thermoplastic resin that is liquid at room temperature and normal pressure can be used as the liquid resin. And, for example, the other resin includes an acrylic resin, an epoxy resin, a silicone resin, a fluororesin, an acrylonitrile-butadiene copolymer, and polybutene, which are compounds different from the above-mentioned crosslinkable resin and are liquid thermoplastic resins at room temperature and normal pressure.
[0027] [Crosslinking Agent] The crosslinking agent is not particularly limited as long as it can undergo a crosslinking reaction with the above-mentioned crosslinkable resin, and is not limited as long as it can be used as a crosslinking agent for the resin. Representative crosslinking agents include sulfur-based crosslinking agents, peroxides, and amine-based crosslinking agents that crosslink the unsaturated bonds contained in the resin. These may be used alone or in combination of two or more types in any ratio. Among these, when the crosslinkable resin is an acrylic polymer, it is preferable to use an amine-based crosslinking agent, and when the crosslinkable resin is at least one of an acrylonitrile-butadiene copolymer and a styrene-butadiene copolymer, it is preferable to use a sulfur-based crosslinking agent.
[0028] The amount of the crosslinking agent is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 5.0 parts by mass or less, and more preferably 2.5 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking agent is within the above range, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, and it is considered that the thermal conductive sheet is provided with appropriate strength and elasticity, thereby maintaining the orientation structure of the boron nitride particles well inside the thermal conductive sheet and enabling the thermal conductive sheet to well follow the expansion and contraction of the member to which it is applied.
[0029] [Crosslinking Accelerator] The crosslinking accelerator that can be used in the crosslinking reaction between the crosslinkable resin and the crosslinking agent is not particularly limited, and a sulfenamide crosslinking accelerator can be used. These may be used alone or in combination of two or more in any ratio. Among them, the sulfenamide crosslinking accelerator is preferred.
[0030] The amount of the crosslinking accelerator is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 parts by mass or more, and preferably 5.0 parts by mass or less, and more preferably 4.0 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking accelerator is within the above range, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, and it is considered that the orientation structure of the boron nitride particles inside the heat conductive sheet is well maintained by imparting appropriate strength and elasticity to the heat conductive sheet, and the heat conductive sheet can well follow the expansion and contraction of the member to which it is applied.
[0031] [Ratio of crosslinked resin content] The proportion of the crosslinked resin contained in the thermal conductive sheet must be 50% by volume or less, preferably 10% by volume or more, more preferably 15% by volume or more, even more preferably 30% by volume or more, and particularly preferably 40% by volume or more, based on the total volume of the resin and the boron nitride particles. If the proportion of the crosslinked resin based on the total volume of the resin and the boron nitride particles is equal to or greater than the lower limit, the thermal conductive sheet will have even greater durability in thermal conductivity. The amount of the cross-linking resin contained in the thermally conductive sheet usually coincides with the amount of the cross-linking resin used in the production of the thermally conductive sheet.
[0032] [Content of other resins] The ratio of the other resin contained in the thermal conductive sheet is preferably 30 mass % or less, more preferably 25 mass % or less, and even more preferably 15 mass % or less, based on the total mass of the resin and boron nitride particles contained in the thermal conductive sheet. The thermal conductive sheet may not contain other resins.
[0033] <Boron nitride particles> The volume average particle diameter of the boron nitride particles is preferably 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, preferably 60 μm or less, more preferably 50 μm or less, and even more preferably 40 μm or less. If the volume average particle diameter of the boron nitride particles is above the above lower limit, it is presumed that the heat transfer path of the boron nitride particles in the heat conductive sheet can be well formed, and the thermal conductivity of the heat conductive sheet can be improved. On the other hand, if the volume average particle diameter of the boron nitride particles is below the above upper limit, the thickness precision of the heat conductive sheet can be sufficiently high. In addition, if the volume average particle diameter of the boron nitride particles is within the above specified range, the durability of the thermal conductivity of the heat conductive sheet can be further improved. In the present invention, the "volume average particle size" can be measured in accordance with JIS Z8825, and refers to the particle size at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by a laser diffraction method.
[0034] The aspect ratio (major axis / minor axis) of the boron nitride particles is preferably more than 1 and not more than 10, and more preferably more than 1 and not more than 5. When the aspect ratio of the boron nitride particles is more than 1 and not more than 10, it is presumed that the boron nitride particles are more likely to be well oriented in the thickness direction in the thermal conductive sheet, and the thermal conductivity in the thickness direction of the thermal conductive sheet can be increased. In the present invention, the "aspect ratio" can be determined by observing boron nitride particles with a SEM (scanning electron microscope), measuring the maximum diameter (long diameter) and the particle diameter (short diameter) in a direction perpendicular to the maximum diameter for any 50 boron nitride particles, and calculating the average ratio of the long diameter to the short diameter (long diameter / short diameter). In the above, for example, when the boron nitride particles are scaly, the "long diameter" refers to the length in the direction of the long axis of the main surface of the scaly shape, and the "short diameter" refers to the length in the direction perpendicular to the long axis of the main surface.
[0035] <<Boron nitride particle content>> The content of boron nitride particles in the thermal conductive sheet must be 50% by volume or more, more preferably 60% by volume or more, and preferably 70% by volume or less, based on the total of the resin and the boron nitride particles. If the content of boron nitride particles in the thermal conductive sheet is equal to or more than the lower limit, the thermal conductive sheet can have high dielectric breakdown resistance, and the thermal conductivity itself and the durability of the thermal conductivity can be further improved. If the content of boron nitride particles in the thermal conductive sheet is equal to or less than the upper limit, the thermal conductive sheet can be effectively prevented from separating into strips due to defects, and the integrity of the thermal conductive sheet can be improved, particularly when the thermal conductive sheet has a structure in which strips are joined in parallel.
[0036] <Other ingredients> The thermal conductive sheet of the present invention may further contain optional components other than the above-mentioned resin and boron nitride particles (hereinafter, sometimes referred to as "other components"). The other components are not particularly limited as long as they are components that can be used in the manufacture of a thermal conductive sheet, and examples thereof include fibrous carbon materials; flame retardants such as red phosphorus flame retardants and phosphate ester flame retardants; plasticizers such as fatty acid ester plasticizers; toughness improvers such as urethane acrylate; moisture absorbents such as calcium oxide and magnesium oxide; adhesion improvers such as silane coupling agents, titanium coupling agents, and acid anhydrides; wettability improvers such as nonionic surfactants and fluorine surfactants; ion trapping agents such as inorganic ion exchangers; and anti-aging agents.
[0037] <Thermal Conduction Sheet Structure> The thermally conductive sheet of the present invention has a structure in which the above-mentioned boron nitride particles are oriented at an orientation angle of 60° to 90° with respect to the main surface of the thermally conductive sheet. If the boron nitride particles are oriented in the thickness direction of the thermally conductive sheet, the thermal conductivity in the thickness direction of the thermally conductive sheet can be increased.
[0038] The orientation angle of the boron nitride particles is preferably 70° or more, more preferably 75° or more, and even more preferably 78° or more. If the orientation angle of the boron nitride particles is equal to or more than the lower limit, the thermal conductivity of the thermal conductive sheet can be improved.
[0039] <Thermal Conduction Sheet Properties> <<Recovery rate>> The thermal conductive sheet of the present invention is required to have a recovery rate of 60% or more, calculated according to the following formula (1), where T1 (mm) is the initial thickness of the thermal conductive sheet, T2 (mm) is the thickness during pressure, which is the thickness of the thermal conductive sheet when it is pressurized for 10 seconds under conditions of a temperature of 100°C and 1 MPa, and T3 (mm) is the post-pressure thickness, which is the thickness of the pressed thermal conductive sheet 1 minute after the load is removed. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1) The recovery rate is an index that indicates the degree to which a material can be restored after being unloaded from a state compressed by a specified method. If the recovery rate is 60% or higher, the thermal conductive sheet can well follow the expansion and contraction of the material to which it is applied, which ultimately results in improved durability of the thermal conductivity.
[0040] Furthermore, the value of the restoration rate is preferably 60% or more, more preferably 80% or more, and even more preferably 90% or more. If the value of the restoration rate is equal to or more than the above lower limit, it can better conform to the member, and as a result, the durability of the thermal conductivity can be further improved. The upper limit of the restoration rate is not particularly limited, and may be, for example, 100%. The value of the restoration rate can be controlled depending on the composition, manufacturing method, etc. of the thermal conductive sheet.
[0041] <<Compression ratio>> Furthermore, the thermal conductive sheet of the present invention preferably has a compression rate calculated according to the following formula (2) of 12% or more, more preferably 14% or more, and preferably 42% or less, more preferably 30% or less. Compression rate (%) = (1 - (T2 ÷ T1)) × 100 (%) (2) Here, T1 and T2 have the following meanings. T1(mm): Initial thickness of the thermal conductive sheet T2 (mm): The thickness during pressure applied to the thermal conductive sheet when it is pressurized for 10 seconds at a temperature of 100°C and 1 MPa.
[0042] If the compression ratio is equal to or greater than the lower limit, the thermally conductive sheet has excellent adhesion to the heat generating body and the heat dissipating body. If the compression ratio is equal to or less than the upper limit, the thermally conductive sheet has appropriate strength and excellent durability. The compression ratio can be controlled according to the composition, manufacturing method, etc. of the thermally conductive sheet.
[0043] <<Thermal conductivity>> The thermal conductivity of the thermal conductive sheet in the thickness direction is preferably 15 W / m K or more, and more preferably 20 W / m K or more. The upper limit of the thermal conductivity of the thermal conductive sheet in the thickness direction is not particularly limited, but is, for example, 45 W / m K or less. The thermal conductivity of the thermal conductive sheet in the thickness direction can be adjusted by the types and proportions of materials and components contained in the thermal conductive sheet, as well as the manufacturing method and manufacturing conditions of the thermal conductive sheet.
[0044] <Thickness of thermal conductive sheet> The thickness of the thermally conductive sheet of the present invention is not particularly limited, but is preferably 50 μm or more, more preferably 100 μm or more, more preferably 200 μm or more, and preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. If the thickness of the thermally conductive sheet is equal to or greater than the above lower limit, the thermally conductive sheet is not excessively thinned, and the strength and handling properties of the thermally conductive sheet can be improved. If the thickness of the thermally conductive sheet is equal to or less than the above upper limit, the thermal conductivity of the thermally conductive sheet in the thickness direction can be improved.
[0045] (Method of manufacturing thermal conductive sheet) The thermal conductive sheet of the present invention can be efficiently manufactured by a manufacturing method including: (A) a pre-thermal conductive sheet forming step of pressurizing a composition containing a resin containing a crosslinkable resin, boron nitride particles, and a crosslinking agent to form a sheet to obtain a pre-thermal conductive sheet; (B) a laminate forming step of stacking a plurality of pre-thermal conductive sheets in the thickness direction or folding or rolling the pre-thermal conductive sheet to obtain a laminate; (C) a slicing step of slicing the laminate at an angle of 45° or less with respect to the stacking direction to obtain a thermal conductive sheet; and (D) a crosslinking reaction step of heating the obtained thermal conductive sheet while pressurizing it in the thickness direction to perform a crosslinking reaction. The thermal conductive sheet of the present invention may further include any of the steps other than the above (A) to (D).
[0046] <(A) Pre-heat conductive sheet molding process> In the pre-thermal conductive sheet molding step, a composition containing a resin containing a crosslinkable resin, boron nitride particles, and a crosslinking agent is pressed and molded into a sheet to obtain a pre-thermal conductive sheet.
[0047] <<Composition>> The composition includes a resin containing a crosslinkable resin, boron nitride particles, and a crosslinking agent. The composition may further include a crosslinking accelerator. Furthermore, the composition may further include components (other components) other than the above-mentioned resin, boron nitride particles, crosslinking agent, and crosslinking accelerator.
[0048] 〔resin〕 Here, the resin contained in the composition contains a crosslinkable resin, and optionally contains a resin other than the crosslinkable resin. As the crosslinkable resin, for example, the crosslinkable resin that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used in the ratio described above. The blending amount of the crosslinkable resin in the composition corresponds to the blending range described for the "content ratio of the crosslinked resin" contained in the thermal conductive sheet described above. In addition, as the resin other than the crosslinkable resin, for example, the resin other than the crosslinkable resin (other resin) that can be contained in the resin described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0049] [Boron nitride particles] As the boron nitride particles, for example, the boron nitride particles described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0050] [Crosslinking Agent] As the crosslinking agent, the crosslinking agents that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used in the proportions described above.
[0051] [Crosslinking Accelerator] As the crosslinking accelerator, those mentioned in the section "Thermal Conductive Sheet" can be used in the proportions mentioned above.
[0052] [Other ingredients] As other components that can be contained in the composition, other components that can be contained in the thermally conductive sheet described above in the section "Thermal Conductive Sheet" can be used.
[0053] [Preparation of Composition] The composition is not particularly limited and can be prepared by mixing the above-mentioned components. The mixing of the above-mentioned components is not particularly limited, and can be performed using known mixing devices such as a kneader; a mixer such as a Henschel mixer, a Hobart mixer, or a high-speed mixer; a twin-screw kneader; or a roll. The mixing may be performed in the presence of a solvent such as ethyl acetate. The resin may be dissolved or dispersed in a solvent in advance to prepare a resin solution, which is then mixed with the boron nitride particles and the crosslinking agent, as well as an optionally added crosslinking accelerator and other components. The mixing time may be, for example, 5 minutes or more and 60 minutes or less. The mixing temperature may be, for example, 5°C or more and 150°C or less.
[0054] <<Molding of the composition>> The composition prepared as described above can be optionally degassed and crushed, and then pressed to form into a sheet. The sheet-shaped composition thus pressurized can be used as a pre-heat conductive sheet. If a solvent is used during mixing, it is preferable to remove the solvent before forming into a sheet. For example, if degassing is performed using vacuum degassing, the solvent can be removed at the same time as degassing.
[0055] Here, the composition can be molded into a sheet using a known molding method such as press molding, rolling molding, or extrusion molding, without any particular limitation, as long as the molding method is one in which pressure is applied. Among them, the composition is preferably molded into a sheet by rolling molding (primary processing), and more preferably molded into a sheet by a predetermined roll molding in which the composition is passed between a first roll and a second roll having a faster peripheral speed than the first roll. The peripheral speed ratio of the second roll to the first roll ("peripheral speed of the second roll" / "peripheral speed of the first roll") is preferably 1.03 / 1 or more and 2 / 1 or less. In addition, the distance between the first roll and the second roll can be, for example, 1 mm or more and 3 mm or less.
[0056] <<Pre-heat conductive sheet>> Furthermore, in the pre-thermal conductive sheet formed by pressing the composition into a sheet, the boron nitride particles are primarily oriented in the in-plane direction, and it is presumed that this particularly improves the thermal conductivity of the pre-thermal conductive sheet in the in-plane direction.
[0057] <(B) Laminate formation process> In the laminate formation step, a plurality of pre-thermally conductive sheets obtained in the pre-thermally conductive sheet forming step are laminated in the thickness direction, or the pre-thermally conductive sheet is folded or rolled to obtain a laminate in which a plurality of thermally conductive sheets containing resin and boron nitride particles are formed in the thickness direction. Here, the formation of the laminate by folding the pre-thermally conductive sheet is not particularly limited, and can be performed by folding the pre-thermally conductive sheet at a constant width using a folding machine. In addition, the formation of the laminate by rolling the pre-thermally conductive sheet is not particularly limited, and can be performed by rolling the pre-thermally conductive sheet around an axis parallel to the short side or long side of the pre-thermally conductive sheet. In addition, the formation of the laminate by stacking the pre-thermally conductive sheets is not particularly limited, and can be performed using a lamination device.
[0058] In the lamination step, the obtained laminate (hereinafter, sometimes referred to as the first laminate) is preferably pressurized in the lamination direction (secondary pressurization) while being heated at a temperature lower than the heating temperature in the crosslinking reaction step described later to form a second laminate. By performing the secondary pressurization in which the laminate is pressurized in the lamination direction while being heated at a temperature lower than the heating temperature in the crosslinking reaction step described later, and then performing the crosslinking reaction step described later, the crosslinking reaction can be performed in a state in which fusion between the pre-thermal conductive sheets is promoted, and therefore the crosslinking strength between the interfaces of the strips (corresponding to the pre-thermal conductive sheets) constituting the thermal conductive sheet can be improved.
[0059] Here, the pressure when pressing the laminate in the stacking direction can be 0.05 MPa or more and 0.90 MPa or less. Alternatively, isostatic pressing can be performed using an apparatus such as an autoclave. The pressure of the isostatic pressing is preferably in the range of 0.3 MPa or more and 0.9 MPa or less.
[0060] Furthermore, the heating temperature of the laminate is not particularly limited as long as it is lower than the heating temperature in the crosslinking reaction step described below, but can be less than 90°C, preferably 85°C or less, and more preferably 80°C or less, and can be 30°C or more, preferably 40°C or more, and more preferably 50°C or more. Furthermore, the heating time for the laminate can be, for example, from 10 seconds to 30 minutes.
[0061] In addition, in the laminate obtained by stacking, folding or rolling the pre-thermal conductive sheet, it is presumed that the boron nitride particles are oriented in a direction approximately perpendicular to the stacking direction.
[0062] <(C) Slicing process> In the slicing step, the laminate obtained in the laminate forming step is sliced at an angle of 45° or less with respect to the lamination direction to obtain a thermally conductive sheet consisting of slices of the laminate. Here, the method for slicing the laminate is not particularly limited, and examples thereof include a multi-blade method, a laser processing method, a water jet method, and a knife processing method. In addition, the cutting tool used when slicing the laminate is not particularly limited, and a slicing member having a smooth plate surface with slits and a blade portion protruding from the slit portion (for example, a plane or slicer with a sharp blade) can be used.
[0063] From the viewpoint of increasing the thermal conductivity of the thermal conduction sheet, the angle at which the laminate is sliced is preferably 30° or less with respect to the stacking direction, more preferably 15° or less with respect to the stacking direction, and preferably approximately 0° with respect to the stacking direction (i.e., in the direction along the stacking direction).
[0064] In the thermally conductive sheet thus obtained, the boron nitride particles are oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the thermally conductive sheet, and the thermal conductivity in the thickness direction is excellent.
[0065] <(D) Crosslinking reaction step> In the crosslinking reaction step, the thermally conductive sheet obtained in the slicing step is heated while being pressed in the thickness direction to cause a crosslinking reaction, which causes a crosslinking reaction between the crosslinkable resin and the crosslinked body to form a crosslinked resin, thereby improving the sheet strength of the thermally conductive sheet and, as a result, increasing the durability of the thermal conductivity of the thermally conductive sheet.
[0066] Here, the pressure when the thermally conductive sheet is pressed in the thickness direction during the crosslinking reaction is preferably 0.1 MPa or more, more preferably 0.3 MPa or more, preferably 1.0 MPa or less, and more preferably 0.6 MPa or less. If the pressure when the thermally conductive sheet is pressed in the thickness direction is equal to or more than the above lower limit, the sheet strength of the thermally conductive sheet can be improved, thereby further increasing the durability of the thermal conductivity of the thermally conductive sheet. On the other hand, if the pressure when the thermally conductive sheet is pressed in the thickness direction is equal to or less than the above upper limit, the thermally conductive sheet can be prevented from being excessively crushed, and the orientation structure of the boron nitride particles can be prevented from collapsing.
[0067] In addition, examples of the method of applying pressure include applying pressure only to the upper and lower two sides of the thermally conductive sheet in the thickness direction, or applying pressure to the upper and lower two sides of the thermally conductive sheet in addition to the side surfaces in the thickness direction. However, from the viewpoint of releasing the gas generated during the crosslinking reaction, it is preferable to apply pressure only to the upper and lower two sides of the thermally conductive sheet in the thickness direction. Examples of the method of applying pressure include a method in which a release film is placed on the upper and lower surfaces of the thermally conductive sheet, and metal plates are placed on the outside of the upper and lower release films, respectively, and the corners of the metal plates are screwed. In this case, the release film may be any film that has excellent releasability and sufficient durability under the heating temperature conditions in the crosslinking reaction process, and a polyimide film or the like can be used. In addition, the metal plate is not particularly limited, but examples of the metal plate include an aluminum plate and a copper plate.
[0068] The heating temperature in the crosslinking reaction step is not particularly limited, but is preferably higher than 140°C, more preferably 150°C or higher, even more preferably 170°C or higher, and preferably 210°C or lower, more preferably 190°C or lower. If the heating temperature in the crosslinking reaction step is equal to or higher than the lower limit, the crosslinking reaction can be carried out well, improving the sheet strength of the produced thermal conductive sheet and further enhancing the durability of the thermal conductivity of the thermal conductive sheet. If the heating temperature in the crosslinking reaction step is equal to or lower than the upper limit, deterioration of the resin constituting the thermal conductive sheet can be suppressed and the durability of the thermal conductivity can be further enhanced.
[0069] The heating time in the crosslinking reaction step is not particularly limited, but may be, for example, 1 hour or more and 6 hours or less. If the heating time in the crosslinking reaction step is equal to or more than the lower limit, the crosslinking reaction is carried out well, thereby improving the sheet strength of the produced thermal conductive sheet and further increasing the durability of the thermal conductivity of the thermal conductive sheet. On the other hand, if the heating time in the crosslinking reaction step is equal to or less than the upper limit, the crosslinking reaction is prevented from proceeding excessively, and the flexibility of the thermal conductive sheet can be well maintained, and as a result, the durability of the thermal conductivity of the thermal conductive sheet can be further increased.
[0070] Even in the thermally conductive sheet that has undergone the above-mentioned crosslinking reaction, the boron nitride particles are oriented at an angle of 60° to 90° with respect to the main surface of the thermally conductive sheet, resulting in excellent thermal conductivity. Furthermore, the crosslinking process gives the thermally conductive sheet itself mechanical strength, and the boron nitride orientation structure is also strengthened, resulting in excellent durability of thermal conductivity. EXAMPLES
[0071] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In each example and each comparative example, various attributes were measured or evaluated by the following methods.
[0072] <Orientation angle of boron nitride> The orientation angle of boron nitride in the thermal conductive sheet obtained in each Example and Comparative Example was obtained by observing the cross section of the thermal conductive sheet cut into a regular octagon with a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, "SU-3500") at a magnification that fits the top to bottom of the sheet. The magnification was 700 times. Specifically, 50 lines were drawn on the long axis of boron nitride in the cross section, and the average angle of the long axis with respect to the surface of the thermal conductive sheet was calculated. If the angle was 90° or more, the supplementary angle was used. This was performed for 8 faces, and the largest value among the 8 faces was taken as the orientation angle of boron nitride in the thermal conductive sheet.
[0073] <Thermal conductivity> [Thermal diffusivity in the thickness direction α] The thermal diffusivity of the thermal conductive sheet was measured using a thermal diffusivity / thermal conductivity measuring device (ai-Phase Mobile 1u, manufactured by Ai-Phase Corporation) in accordance with the provisions of ISO22007-3. [Specific heat at constant pressure Cp] The specific heat was measured at 25° C. under a temperature increase rate of 10° C. / min using a differential scanning calorimeter (manufactured by Rigaku, product name "DSC8230"). [Specific gravity ρ (density)] The measurement was performed using an automatic specific gravity meter (manufactured by Toyo Seiki Co., Ltd., product name "DENSIMETER-H"). Then, each measured value is calculated using the following formula (I): λ = α × Cp × ρ (I) The thermal conductivity λ (W / m K) in the thickness direction of the thermal conductive sheet at 25°C was calculated by substituting
[0074] <Voltage test value> The withstand voltage test values of the thermally conductive sheets manufactured in the examples and comparative examples were measured using an in-oil test device (manufactured by Tama Densoku Co., Ltd., product name "TJ-20S"). Specifically, a thermally conductive sheet cut into a roughly 3 cm square was used as a sample, and the sample was immersed in silicone oil at 23°C. One minute after immersion, voltage application was started at a voltage increase rate of 0.6 kV / sec, and the voltage (kV) was measured when the current (detection current) flowing through the sample reached 10 mA. The obtained voltage (kV) value was divided by the thickness (mm) of the thermally conductive sheet sample to obtain a voltage resistance test value (kV / mm). A higher voltage resistance test value indicates that the thermally conductive sheet has better resistance to dielectric breakdown.
[0075] <Restoration rate and compression rate> The thermally conductive sheets produced in the examples and comparative examples were evaluated for compressibility and restorability using a probe tack tester (manufactured by Rhesca Corporation, product name "TAC1000"). Specifically, a flat probe with a diameter of 7 mm was pressed against a heat conductive sheet punched into a circle with a diameter of 5 mm for 10 seconds at 100°C and 1 MPa. The initial thickness T1 (mm) of the heat conductive sheet, the thickness during pressure T2 (mm) which is the thickness of the film when pressure was applied for 10 seconds under the above conditions, and the thickness after pressure T3 (mm) which is the thickness 1 minute after the pressured heat conductive sheet was unloaded were measured, and the values were calculated as follows. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1) Compression rate (%) = (1 - (T2 ÷ T1)) × 100 (%) (2)
[0076] <Durability of thermal conductivity> A test piece measuring 25 mm × 25 mm × 0.30 mm was cut out from the thermally conductive sheets produced in the Examples and Comparative Examples. The test piece was sandwiched between a copper plate measuring 50 mm × 50 mm × 8 mm and an aluminum plate of the same size, and the four corners were secured with screws to produce a copper plate-thermally conductive sheet-aluminum plate structure. The structure was created so that a pressure of 0.6 MPa was applied to the sheet by adjusting the screws at the four corners, and this structure was kept at 175°C for 24 hours. After that, the structure was cooled to room temperature, and the pressure of the screws was adjusted to 0.3 MPa and it was kept in an atmosphere of 175°C for another 24 hours, which constituted one cycle. Here, the 8 mm thick copper and aluminum plates do not normally deform significantly, but by changing the pressure applied to the structure, the thermal expansion in the operating environment of an electronic device was reproduced in a pseudo manner. The test pieces used in the above tests were evaluated using a transient thermal resistance measuring device (manufactured by Siemens, product name "T3Ster") to evaluate the thermal resistance of the copper plate-thermal conductive sheet-aluminum plate structure, and the thermal resistance of the initial structure was compared with that of the structure after 20 cycles. The higher the thermal conductivity retention rate (%) calculated according to the formula below, the more excellent the thermal conductivity durability of the thermal conductive sheet is. (Thermal resistance maintenance rate%) = 100 x {1 - (thermal resistance after 20 cycles - initial thermal resistance) ÷ initial thermal resistance}
[0077] Example 1 <Preparation of Composition> As the crosslinkable resin, an acrylic rubber, which is a solid acrylic resin at room temperature and normal pressure (manufactured by Zeon Corporation, product name "Nipol (registered trademark) AR-12", glass transition temperature: -30.3°C, specific gravity: 1.1 g / cm 3 210 parts of hexagonal boron nitride (h-BN) (manufactured by Dandong Chemical Engineering, product name "HSL-HP50", aspect ratio: 1.5, specific gravity: 2.23) as boron nitride particles, which is plate-like (scale-like) boron nitride, were kneaded for 20 minutes at a temperature of 120°C using a pressure kneader (manufactured by Nippon Spindle) to obtain a composition. 3.2 parts of Nocrac 224 as an anti-aging agent, 1.05 parts of Diak#1 (manufactured by Chemours) as a crosslinking agent, and 4.2 parts of Noccela DT as a crosslinking accelerator were added to the obtained composition, and the mixture was kneaded for 5 minutes at a temperature of 80°C to obtain a composition.
[0078] <Pre-heat conductive sheet forming process> Next, 500 g of the obtained composition was rolled into a sheet using a first roll and a second roll under the following conditions: a gap between the first roll and the second roll of 1 mm, a roll temperature of 25° C., a sheet discharge speed (peripheral speed of the first roll) of 2 m / min, and a peripheral speed ratio of the second roll to the first roll (second roll / first roll): 1.15 / 1. The rolling process was repeated while keeping the sheet conveying direction the same. The rolling process was performed 10 times in total to obtain a pre-heat-conductive sheet having a thickness of 1 mm.
[0079] <First laminate formation process> Next, the obtained pre-thermal conductive sheet was cut into a size of 50 mm length×50 mm width, and 50 sheets were stacked in the thickness direction to obtain a first stack having a height of about 50 mm.
[0080] <Second laminate formation process> The obtained first laminate was wrapped in release PET (polyethylene terephthalate), taped, and vacuum-packaged in a PET retort package. This was heated and pressurized for 30 minutes in an autoclave (Hanyu Iron Works, small autoclave "DANDELION") at a temperature of 80°C and a pressure of 0.8 MPa (absolute pressure) from all directions to obtain a second laminate.
[0081] <Slicing process> Next, while pressing the laminated surface of the secondary pressurized laminate with a pressure of 0.3 MPa, a wood slicer (Marunaka Iron Works, product name "Super Finish Planer Super Mecha S") was used to slice at an angle of 0 degrees to the lamination direction (in other words, in the normal direction of the main surface of the laminated primary sheets) to obtain a secondary sheet (thermal conductive sheet) of length 50 mm x width 50 mm x thickness 0.30 mm. The thermal conductive sheet is composed of strips joined in parallel in a direction perpendicular to the thickness direction of the thermal conductive sheet (a direction at an angle of 90° to the thickness direction). The width of the strips in this approximately perpendicular direction is approximately the same as the thickness of the pre-thermal conductive sheet.
[0082] <Crosslinking reaction process> The obtained thermal conductive sheet was sandwiched between release films on both sides to prevent adhesion, and then sandwiched between a 70mm x 70mm x 8mm copper plate and a 70mm x 70mm x 8mm aluminum plate, and the four corners were secured with screws to create a copper plate-thermal conductive sheet-aluminum plate structure. The screw pressure was adjusted so that a pressure of 0.3MPa was applied to the sheet in the thickness direction. This structure was subjected to a crosslinking reaction in air for 2 hours at 175° C. After the reaction, the structure was taken out and the release film was peeled off to obtain a thermally conductive sheet. The thermally conductive sheet thus obtained was subjected to various measurements and evaluations as described above. The results are shown in Table 1.
[0083] (Examples 2 and 3) In <Preparation of Composition>, the same operations, measurements, and evaluations as in Example 1 were carried out, except that the amounts of the various components were changed as shown in Table 1. The results are shown in Table 1.
[0084] Example 4 The crosslinkable resin to be blended was an acrylic rubber (manufactured by Zeon Corporation, product name "Nipol (registered trademark) AR-14", glass transition temperature: -42.0°C, specific gravity: 1.1 g / cm) which is a solid acrylic resin at room temperature and normal pressure. 3 ) was used. Except for this, the same operations, measurements, and evaluations as in Example 2 were carried out. The results are shown in Table 1.
[0085] Example 5 The blending amount of the acrylic resin was 75 parts, and the other resin that was not a crosslinkable resin was liquid nitrile butadiene rubber (hereinafter also referred to as "liquid NBR") (Nipol 1312, manufactured by Nippon Zeon, specific gravity: 1 g / cm 3) was blended in 75 parts (12% by mass based on the total mass of the crosslinkable resin, other resins, and scaly filler), and the blending amount of boron nitride particles was 480 parts. Other components (antiaging agent, crosslinking agent, and crosslinking accelerator) were also changed as shown in Table 1. Note that liquid NBR does not react with Diak#1 blended as a crosslinking agent for acrylic rubbers AR-12 and AR-14, so it essentially plays a role like a plasticizer. Other than the above, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0086] Example 6 The blending ratio of acrylic resin was 43 parts, and liquid NBR (Nipol 1312, manufactured by Zeon Corporation, specific gravity: 1 g / cm) was used as other resin that is not a cross-linking resin. 3 ) was 100 parts (17% by mass based on the total mass of the crosslinkable resin, other resins, and scaly filler), and the amount of boron nitride particles was 460 parts. Other components (antiaging agent, crosslinking agent, and crosslinking accelerator) were also changed as shown in Table 1. Liquid NBR does not react with Diak#1, which is mixed as a crosslinking agent for acrylic rubbers AR-12 and AR-14, so it essentially plays a role like a plasticizer. Other than the above, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0087] Example 7 As the crosslinkable resin, solid nitrile butadiene rubber (hereinafter also referred to as "solid NBR") (Nipol3350: manufactured by Nippon Zeon Co., Ltd., Mooney viscosity: 50, glass transition temperature: -38.0°C, specific gravity: 1 g / cm 3 ) was used in an amount of 180 parts. The amount of boron nitride particles was 590 parts, and Nocrac 224 as an anti-aging agent was 2.7 parts. Furthermore, 5.4 parts of zinc oxide as a vulcanization activator, 1.8 parts of stearic acid as a vulcanization activator, 2.7 parts of sulfur (Kinkaji Fine Sulfur 325 Mesh: manufactured by Tsurumi Chemical Industry Co., Ltd.) as a sulfur-based crosslinking agent, and 3.6 parts of Noccela CZ-G as a crosslinking accelerator were mixed. Except for the above points, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0088] Example 8 As the crosslinkable resin, a styrene butadiene rubber (hereinafter also referred to as "solid SBR") that is solid at room temperature and normal pressure (Nipole 1502, manufactured by Nippon Zeon Co., Ltd., glass transition temperature: -50°C, specific gravity: 0.94 g / cm) was used. 3 ) was used. The amount of boron nitride particles was 630 parts, and Nocrac 224 as an anti-aging agent was 2.7 parts. Furthermore, 5.4 parts of zinc oxide as a vulcanization activator, 1.8 parts of stearic acid as a vulcanization activator, 2.7 parts of sulfur (Kinkaji Fine Sulfur 325 Mesh: manufactured by Tsurumi Chemical Industry Co., Ltd.) as a sulfur-based crosslinking agent, and 3.6 parts of Noccela CZ-G as a crosslinking accelerator were mixed. Except for the above points, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0089] Comparative Example 1 The amount of acrylic rubber as a thermoplastic resin was 168 parts, the amount of boron nitride particles was 720 parts, the amount of antioxidant was 2.5 parts, and no other ingredients were added. In addition, 30 parts of bisphenol F type epoxy resin (manufactured by Tohto Kasei Co., Ltd., product name: YDF-8170C, epoxy equivalent: 156g / eq.) was added as an epoxy resin curing agent, 32 parts of xylene-modified phenol novolac resin (manufactured by Mitsui Chemicals, Inc., product name: Milex XLC-LL, hydroxyl equivalent: 172g / eq.) was added as an epoxy resin curing agent, and 0.3 parts of 1-cyanoethyl-2-phenylimidazole (manufactured by Shikoku Kasei Co., Ltd., product name: 2PZ-CN) was added as a curing accelerator. The results are shown in Table 1.
[0090] Comparative Example 2 Except for not adding the crosslinking agent and the crosslinking accelerator, the same operations, measurements, and evaluations were carried out as in Example 2. The results are shown in Table 1.
[0091] [Table 1]
[0092] From Table 1, it can be seen that in the thermal conductive sheets containing a resin including a crosslinked resin and boron nitride in a predetermined volume ratio, in which the boron nitride is oriented at a predetermined orientation angle within the sheet, the thermal conductive sheets of Examples 1 to 8, in which the value of the recovery rate calculated according to a predetermined formula is 60% or more, have excellent durability of thermal conductivity. On the other hand, it is understood that the thermally conductive sheets of Comparative Examples 1 and 2, which had a recovery rate value of less than 60%, were inferior in durability of thermal conductivity. [Industrial Applicability]
[0093] According to the present invention, it is possible to provide a thermally conductive sheet having excellent durability in thermal conductivity.
Claims
1. a volume fraction of the boron nitride particles in the total volume of the resin and the boron nitride particles is 50 volume % or more; and the thermal conductive sheet has a recovery rate of 60% or more as calculated according to the following formula (1): T1 (mm) is an initial thickness of the thermal conductive sheet; T2 (mm) is a thickness during pressure which is a thickness of the thermal conductive sheet when the thermal conductive sheet is pressurized for 10 seconds under conditions of a temperature of 100° C. and a pressure of 1 MPa; and T3 (mm) is a thickness after pressure is applied to the thermal conductive sheet one minute after the pressurized sheet is unloaded. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1)
2. 2. The thermal conductive sheet according to claim 1, wherein the crosslinked resin comprises at least one crosslinked product of an acrylic polymer, an acrylonitrile-butadiene copolymer, and a styrene-butadiene copolymer.
3. The thermal conductive sheet according to claim 1 , wherein a volume fraction of the crosslinked resin relative to a total volume of the resin and the boron nitride particles is 10 volume % or more.
4. 2. The thermal conductive sheet according to claim 1, wherein the compressibility calculated according to the following formula (2) is 12% or more and 42% or less. Compression rate (%) = (1 - (T2 ÷ T1)) x 100 (%) ... (2)
5. The thermal conductive sheet according to any one of claims 1 to 4, wherein a voltage is applied to the thermal conductive sheet at a voltage rise rate of 0.6 kV / sec to obtain a voltage V1 (kV) when a current flowing through the thermal conductive sheet becomes 10 mA, and the obtained voltage V1 (kV) is divided by an initial thickness T1 (mm) of the thermal conductive sheet to obtain a voltage withstand test value (kV / mm) of 8 (kV / mm) or more.
Citation Information
Patent Citations
Thermally conductive sheet
JP2018203857A